Teaching Magnetoelectric Sensing to Secondary School Students—Considerations for Educational STEM Outreach - Cara Broß (MDPI AG, 2021)
A major challenge in modern society is the need to increase awareness and excitement with regard to science, technology, engineering and mathematics (STEM) and related careers directly or among peers and parents in order to attract future generations of scientists and engineers. The numbers of students aiming for an engineering degree are low compared to the options available and the workforce needed. This may, in part, be due to a traditional lack of instruction in this area in secondary school curricula. In this regard, STEM outreach programs can complement formal learning settings and help to promote engineering as well as science to school students. In a long-term outreach collaboration with scientists and engineers, we developed an outreach program in the field of magnetoelectric sensing that includes an out-of-school project day and various accompanying teaching materials. In this article, we motivate the relevance of the topic for educational outreach, share the rationales, objectives and aims, models and implementation strategies of our program and provide practical advice for those interested in outreach in the field of magnetoelectric sensing.